2017
DOI: 10.1016/j.psychres.2017.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of Individual Cognitive Behavior Therapy for patients with unipolar mood disorders with suicidal ideation in Malaysia: A randomised controlled trial

Abstract: The aim of this study was to investigate the effectiveness of Individual Cognitive Behavior Therapy (ICBT) in treating patients with mood disorders with suicidal ideation. A total of 69 patients (48 females, 21 males) with the diagnoses above were randomly allocated to either the group of Treatment As Usual (TAU) + ICBT (n=33) or the TAU group (n=36). All participants completed the Beck Depression Inventory (BDI), Beck Scale for Suicide Ideation (BSS), Positive and Negative Suicide Ideation Inventory (PANSI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…The findings of the study indicate that psychosocial intervention, et al (17) in particular CBT, were shown to be effective in the treatment of depressive symptoms. Also the study suggests that CBT is effective in treatment of depressive symptoms with suicidal ideation.…”
Section: Sinniah No Evaluation Efficientmentioning
confidence: 66%
“…The findings of the study indicate that psychosocial intervention, et al (17) in particular CBT, were shown to be effective in the treatment of depressive symptoms. Also the study suggests that CBT is effective in treatment of depressive symptoms with suicidal ideation.…”
Section: Sinniah No Evaluation Efficientmentioning
confidence: 66%
“…Preventing the detrimental influence of negative affect and enhancing the protective effect of positive affect and presence of meaning in life could increase the effectiveness of prevention and intervention strategies targeting suicidal ideation. Nowadays, cognitive behavior therapy (CBT) has been an effective treatment that is widely used in the intervention of suicidal ideation (Ecker et al, 2019;Kalmbach et al, 2022;Sinniah et al, 2017;Wu et al, 2022). Our findings indicate that CBT strategies targeting on these identified central and bridge nodes may be of benefit for the prevention and intervention of suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…The design development process was steered by the foundation set by Verduyn (2000), Saravanan, Alias &Mohamad (2017), andSinniah et al (2017) who investigated the effectiveness of individual cognitive behaviour therapy in depression. Their research, that is also in accord with numerous research such as treatment approaches for reducing the risk of major depression in adolescence including group cognitive-behavioural and individual interpersonal psychotherapy (Landback et al, 2009), tactile therapy as an effective psychological comfort (Schmidt, 2006;Kamil and Abidin, 2013;Fritz and Fritz, 2020), recovery rates in major depressive disorder patients (Novick et al, 2017), study of shape, colour and lights as a therapy for depression (Wileman et al, 2001;Loving et al, 2005;Kim and Kang, 2013;Roseman-Halsband, 2018;Hajra and Saleem, 2021), finds that the integration of tactile sensory, colours and design elements in cognitive behaviour therapy have significant potential to elevate comfort among adolescent with depressive disorder.…”
Section: Methodsmentioning
confidence: 99%